Dengue fever complicated with acute ST elevation myocardial infarction - a therapeutic conundrum: our experience from two cases - Wijayabandara, Maheshi; Wijesundara, Devasmitha; Gamakaranage, Champika; Karunanayake, Panduka; Fernando, Shyam; Jayasinghe, Saroj (Asian Journal of Medical Sciences, 2021)
Dengue fever has a wide range of clinical manifestations from asymptomatic disease to complicated dengue haemorrhagic fever and dengue shock syndrome. Bleeding manifestations in dengue is well known but thrombotic events complicating dengue is uncommon. ST elevation myocardial infarction during dengue is rare and poses important management dilemma. At present, there is no consensus on how to manage this situation. We present two patients with dengue fever developing ST elevation myocardial infarction and our experience in the management. We suggest case-based management of acute coronary syndrome in dengue, guided by the degree of thrombocytopaenia and bleeding risk. Further studies are needed to include this into existing dengue management guidelines.